Role of primary care in the follow-up of patients with obstructive sleep apnoea undergoing CPAP treatment: a randomised controlled trial. Issue 4 (12th March 2015) - Sánchez-de-la-Torre, M; Nadal, N; Cortijo, A; Masa, JF; Duran-Cantolla, J; Valls, J; Serra, S; Sánchez-de-la-Torre, A; Gracia, M; Ferrer, F; Lorente, I; Urgeles, M C; et al.
Abstract : Objective: To evaluate whether follow-up of patients with obstructive sleep apnoea (OSA) undergoing CPAP treatment could be performed in primary care (PC) settings. Design: Non-inferiority, randomised, prospective controlled study. Settings: Sleep unit (SU) at the University Hospital and in 8 PC units in Lleida, Spain. Participants: Patients with OSA were randomised to be followed up at the SU or PC units over a 6-month period. Main outcomes measured: The primary outcome was CPAP compliance at 6 months. The secondary outcomes were Epworth Sleep Scale (ESS) score, EuroQoL, patient satisfaction, body mass index (BMI), blood pressure and cost-effectiveness. Results: We included 101 patients in PC ((mean±SD) apnoea–hypopnoea index (AHI) 50.8±22.9/h, age 56.2±11 years, 74% male) and 109 in the SU (AHI 51.4±24.4/h, age 55.8±11 years, 77% male)). The CPAP compliance was (mean (95% CI) 4.94 (4.47 to 5.5) vs 5.23 (4.79 to 5.66) h, p=0.18) in PC and SU groups, respectively. In the SU group, there were greater improvements in ESS scores (mean change 1.79, 95% CI +0.05 to +3.53, p=0.04) and patient satisfaction (−1.49, 95% CI −2.22 to −0.76); there was a significant mean difference in BMI between the groups (0.57, 95% CI +0.01 to +1.13, p=0.04). In the PC setting, there was a cost saving of 60%, with similar effectiveness, as well as a decrease in systolic blood pressure (−5.32; 95% CI −10.91 to +0.28, p=0.06). Conclusions: For patients with OSA, treatment provided in a PC setting did not result in worse CPAP compliance compared with a specialist model and was shown to be a cost-effective alternative. Trial registration number: Clinical Trials NCT01918449 .